Islamic art : past, present, future - Biennial Hamad bin Khalifa Symposium on Islamic Art and Culture 2017 : Virginia Museum of Fine Arts); Bloom, Jonathan (Jonathan M.); Blair, Sheila (New Haven : Yale University Press in association with Qatar Foundation, Virginia Commonwealth University and Virginia Commonwealth University School of the Arts in Qatar, 2019)
'Islamic art can be a challenging term in an ever-changing art world. Through the exploration of a wide array of media-from painting, sculpture, and photography to video and multimedia-an internationally renowned group of scholars, collectors, artists, and curators tackles questions such as whether the art has to come from the Middle East, whether it must have a religious component, and, indeed, whether the work of art must be made by a Muslim. Based on a series of papers presented at the 7th Biennial Hamad bin Khalifa Symposium on Islamic Art in 2017, the essays in this volume grapple with these questions from a range of viewpoints. Taken together, these texts, including beautiful illustrations of major works by contemporary artists from the Muslim world, invoke a lively discussion of how the arts of the Islamic lands link the past with the present and the future.'--Publisher description.
Defining meaning and value in contemporary Islamic Art / H.E. Sheikha Al Mayassa bint Hamad bin Khalifa Al Thani -- Islamic Art Now and Then / Linda Komaroff -- Art and Image / Venetia Porter -- Gender, Power, and Tradition / Lalla Essaydi -- Hub Wahad: On Finding Inspiration in a Community of Nomads / Hassan Hajjaj in conversation with Alice Planel -- Reclaiming Indo-Persian Miniature Painting. Reclaiming History: A Feminist Story / Shahzia Sikander in conversation with Rafia Zakaria -- A Shah, a Russian, and My Grandfather: Iranian Photography, a History / Newsha Tavakolvian -- Contemporary or Modern Islamic Art? / H.R.H. Princess Wijdan Fawaz Al Hashemi -- Whose Past is it Anyway? Contemporary Architecture and the Past in the Lands of Islam / Mohammad al-Asad -- Contemporary Trajectories: Iraqi Art in Context / Nada Shabout -- Iranian Cinema Today: An Ode to the Past and New Directions in the Future? / Nacim Pak-Shiraz -- 'Islamic' Art in Southeast Asia and Australia: Past, Present, and Future / Stefano Carboni -- Question and Answer Panels: Hamad bin Khalifa Symposium on Islamic Art, Virginia Museum of Arts / transcribed by Sarah Kleinman.
'This volume presents the written versions of the papers presented Islamic Art: Past, Present, and Future, the seventh Biennial Hamad bin Khalifa Symposium on Islamic Art and Culture, which was held at the Virginia Museum of Art in Richmond, Virginia, on November 2-4, 2017'--Introduction.
Includes bibliographical references (pages 331-335) and index.
Buku bacaan asas siswazah Fakulti Pengajian Islam.
Keywords: Islamic arts -- Congresses; Islamic art; Art and Design